The Future of American Families: Implications for Social Work Research, Practice, and Education - Karen Kayser (Advances in Social Work, 2005)
In this article I briefly describe the changing face of contemporary families in America, and in particular focus on four areas of social work practice in which a family-centered approach is needed. I then present future suggestions for social work research, practice, and education. This is not meant to be an exhaustive review of the literature nor is it an in-depth analysis of one particular area of families.